A INFLUÊNCIA DOS SUBSISTEMAS DE VEDAÇÃO VERTICAL NO DESEMPENHO ENERGÉTICO DO EDIFÍCIO - Costalonga, Filipe Galina (2020)
The world is becoming increasingly urbanized. In these circumstances, reducing the consumption of energy from buildings is an extremely important aspect for the sustainable development of the new buildings that will be built to supply the accelerated urba